Add‐on cannabidiol significantly decreases seizures in 3 patients with SYNGAP1 developmental and epileptic encephalopathy. Issue 3 (1st July 2020) - Kuchenbuch, Mathieu; D'Onofrio, Gianluca; Chemaly, Nicole; Barcia, Giulia; Teng, Théo; Nabbout, Rima
Abstract: Mutations in SYNGAP1 are associated with developmental delay, epilepsy, and autism spectrum disorder (ASD). Epilepsy is often drug‐resistant in this syndrome with frequent drop attacks. In a prospective study of add‐on cannabidiol (CBD), we identified three patients with SYNGAP1 mutations: two boys and one girl. Seizure onset was at 3.5, 8, and 18 months (M), respectively, with numerous atypical absences per day associated with eyelid myoclonia (2/3 patients), upper limb myoclonic jerks (2/3 patients), and drop attacks (all patients). Seizures were resistant to at least 5 antiepileptic drugs (AEDs). After CBD introduction, two patients were responders since M2 and achieve a seizure reduction of 90% and 80%, respectively, at M9 with disappearance of drop attacks. EEGs showed an improvement regarding background activity and interictal anomalies. The last patient showed a late response at M7 of treatment with an 80% decrease in seizure frequency. Caregiver in all three evaluated as much improved the status of their children. Treatment was well‐tolerated in all, and no major adverse events (AEs) were reported. CBD showed efficacy in patients with drug‐resistant epilepsy due to SYNGAP1 mutations. Other patients with rare genetic developmental and epileptic encephalopathies with drug‐resistant epilepsies might benefit from CBD.